A Randomized, Double Blind, Placebo‐Controlled Trial of an Oral Synbiotic (AKSB) for Prevention of Travelers' Diarrhea. Issue 2 (25th January 2013) - Virk, Abinash; Mandrekar, Jayawant; Berbari, Elie F.; Boyce, Thomas G.; Fischer, Philip R.; Kasten, Mary J.; Orenstein, Robert; Rosenblatt, Jon E.; Sampathkumar, Priya; Sia, Irene; Springer, Donna; Witzig, Thomas E.
<x xml:space="preserve">Abstract</x> Background Travelers' diarrhea (TD) is a significant problem for travelers. TD is treatable once it occurs, but few options for prevention exist. Probiotics have been studied for prevention or treatment of TD; however, very few combination probiotics have been studied. Therefore, the purpose of this study was to determine if prophylactic use of an oral synbiotic could reduce the risk of acquiring TD and reduce antibiotic use if TD occurred. Methods Healthy subjects traveling to an area of the world with an increased risk of TD were eligible. All subjects received pre‐travel counseling and were provided antibiotics and antidiarrheals (loperamide) for use only if TD developed. The subjects were blinded and randomized to take two capsules of placebo or oral synbiotic (a combination of two probiotics and a prebiotic) called Agri‐King Synbiotic (AKSB) beginning 3 days prior to departure, daily while traveling, and for 7 days after return. All subjects kept symptom and medication diaries and submitted a stool sample for pathogen carriage within 7 days of return. The study was powered to detect a 50% reduction in the incidence of TD. Results Of the 196 adults (over 18 years of age) enrolled in the study, 54.3% were female and 80.9% were younger than 60 years. The study randomized 94 people to the AKSB arm and 102 to placebo. The incidence of TD was 54.5% in the overall group with 55.3% in the AKSB arm and 53.9% in the placebo (p = 0.8864). Among the subjects who experienced diarrhea (n = 107) there was no significant difference in the proportion of subjects that took antibiotics versus those that did not take antibiotics (35% vs 29%, p = 0.68). AKSB was safe with no difference in toxicity between the two arms. Conclusions The prophylactic oral synbiotic was safe but did not reduce the risk of developing TD among travelers, nor did it decrease the duration of TD or the use of antibiotics when TD occurred.